Толерантность к низкотемпературному фитопатогену, полученная с использованием метода химического мутагенеза у озимой пшеницы - Эйгес, Н.С.; Волченко, Г.А.; Волченко, С.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Investigations of winter wheat perspective chemomutant varieties and patterns, received by utilization of chemical mutagenesis method on the resistance and tolerance to snow mould. Investigation of the tolerance and regeneration ability in various conditions. Methods. The objects of investigation are the best chemomutant varieties and perspective patterns, received by utilization of the chemical mutagenesis method in comparison with varieties, received by traditional methods only, without the chemical mutagenesis method. Provocative background for discovery the tolerance and resistance to phusariose snow mould was natural only and strong, on the level of epiphitoties. Results. In result of many years investigations in model experiments and in the farmings in various regions of Moscow oblast it was found the number of chemical mutant varieties and patterns, tolerant to snow mould. It determines preservation of the harvest even on low agrobackground of loamy and sandy light soils. It was found that the basis of the tolerance is a high regeneration ability to good bushing and to thick stem standing. Also the chemomutant varieties are the basis of the prophylactic protection of the environment and agricultural production against high toxic phungicides and herbicides. Conclusion. The chemical mutagenesis method of I.A. Rapoport is high effective, including in relation to creation a sign of tolerance to phuzarios snow mould on the basis of mutations complex, which determinates the high regeneration ability and ability to good bushing out and to form thick stem standing. Received data permit to decrease volumes of agricultural chemical weed-killers and pest-killers, or decline of them for prophylactic protection of environment and have ecology pure agricultural production.